Assistance in Converting Tofu Waste Into Valuable Products for the Ngrangin Jaya Tofu and Tempeh Business Group in Sumberpasir Village, Pakis District, Malang Regency. - Suryanto Hertika, Asus Maizar; Nurlaelih, Euis Elih; Amron, Kasyful; Supriyatin, Febriyani Eka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
This article describes the implementation of the Doctoral Program in comunity Service (Doktor mengabdi / DM) conducted in Sumberpasir Village, Pakis District, Malang Regency. The purpose of this service is to empower the community through the utilization of tofu industry waste into useful and eco-friendly products. The program consisted of three main activities: BIOLITA, which focused on processing liquid tofu waste into organic liquid fertilizer; MAGOLITA, which transformed solid tofu waste into maggot feed; and GURAME, which emphasized character building and educational development for elementary school students. The impact of this service involved improving environmental awareness, enhancing waste management practices, promoting community-based economic opportunities, and fostering cooperation between the university and the village. The program successfully demonstrated how higher education institutions can contribute to sustainable community development through applied science and innovation.